Influence of Product Changes and Product Quality on Customer Trust at PT. Pertamina (Case Study: Bagan Batu City) - Maidalena; Wan Frisca Putri; Hendra Harmain (Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of product changes and product quality on customer trust at PT Pertamina Bagan Batu Kota. The background of this study is the phenomenon of fuel product changes carried out by Pertamina as a form of innovation and adjustment to market needs, but often accompanied by issues of fuel mafia practices in the form of adulteration, hoarding, and illegal distribution that can reduce consumer trust. This study adopts a quantitative research approach to examine the effects of product changes and product quality on consumer trust at PT Pertamina, specifically in Bagan Batu City.The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software, which included the evaluation of both the outer model and the inner model. The outer model assesses the relationships between latent variables and their indicators, while the inner model examines the relationships among latent variables. The results show that both product changes and product quality have a positive and significant effect on customer trust. The product change variable has a t-statistic value of 2.214 (p-value 0.027), while product quality has a t-statistic value of 3.679 (p-value 0.000). Simultaneously, both variables are able to explain 66.4% of the variation in customer trust (R² = 0.664).